Critique of the Public Sphere: A Kantian Measure of the Enlightenment of Societies - Hammer, Martin (Con-Textos Kantianos. International Journal of Philosophy, 2021)
I propose a method of assessing the degree of enlightenment of a society based on (specific characteristics of) its discourses. My hypothesis is that the more objectivity prevails in a society’s spheres of discourse, the more enlightened it is; the more subjectivity dominates, the more unenlightened. This relationship can be made evident through the reconstruction of Kant’s Theory of Prejudice by taking into account the handwritten notes and fragments and the lectures on logic. First, I will discuss some key aspects of Kant’s concept of prejudice. Secondly, I will address the epistemological function of the public sphere in order to show what conditions it must satisfy to fulfil its function. Thirdly, I will argue that not only Selbstdenken but also participatory reason (teilnehmende Vernunft), and therefore the public sphere itself, are both fundamental elements of enlightenment in that they function as counter-maxims against prejudice.